Filtration of components of processes of random evolution - Lukin, A. E.; Svishchuk, A. V.; Лукін, О. Е.; Свіщук, А. В. (Institute of Mathematics, NAS of Ukraine, 1998)
The problem of estimation of a nonobservable component θt for a two-dimensional process (θt, ξt) of random evolution (θ t,ξt);xt, 0≤t≤T, is investigated on the basis of observations of ξs. s≤t, where x t is a homogeneous Markov process with infinitesimal operator Q. Applications to stochastic models of a (B,S)-market of securities is described under conditions of incomplete market.